Retail prices of selected materials/ hire rate-per-hour of plant, machinery & equipment/ wages of workers in the building and construction industry (categorised) - Nigeria, National Bureau of Statistics; Nigeria; Federal Government Economic Reform & Governance Project (Nigeria) ([Abuja, Nigeria] : National Bureau of Statistics, 2007)
This is a compilation of all categories of retail prices of selected materials by states, hire-rate per hour of plant, machinery and equipment by states and wages of workers in the building and construction industries by states.
Produced under the auspices of the Economics Reforms & Governance Project (ERGP).
oif 07/02/2020
Ref.
Keywords: Building materials; Construction equipment; Wages; Construction industry; Materials--Prices; Pricing--Government policy; Wages--Construction workers; Wages--Government policy; Wages--Machinery industry; Nigeria